2019
DOI: 10.1145/3355502
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Kernelization for Maximum Independent Sets

Abstract: The most efficient algorithms for finding maximum independent sets in both theory and practice use reduction rules to obtain a much smaller problem instance called a kernel. The kernel can then be solved quickly using exact or heuristic algorithms-or by repeatedly kernelizing recursively in the branch-and-reduce paradigm. It is of critical importance for these algorithms that kernelization is fast and returns a small kernel. Current algorithms are either slow but produce a small kernel, or fast and give a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The algorithm may repeatedly attempt to apply the same reduction to a vertex even though the graph has not changed sufficiently to allow the reduction to succeed. Checking dependencies between reductions [94], allows to avoid applying certain local reductions when they will provably not succeed, e.g. if their relevant neighborhood did not change since the reduction was last checked.…”
Section: Engineering Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithm may repeatedly attempt to apply the same reduction to a vertex even though the graph has not changed sufficiently to allow the reduction to succeed. Checking dependencies between reductions [94], allows to avoid applying certain local reductions when they will provably not succeed, e.g. if their relevant neighborhood did not change since the reduction was last checked.…”
Section: Engineering Techniquesmentioning
confidence: 99%
“…Reduction tracking. The algorithm by Hespe et al [94] stops local reductions when they are not effectively reducing the global graph sizes. It is not always ideal to apply reductions exhaustively-for example, if only few reductions will succeed and they are costly.…”
Section: Engineering Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that it is still infeasible to solve our MIS problem with state of the art algorithms [ 18 , 19 ] when . Segundo et al proposed a variation of BBMC [ 20 ] and found the maximum independent set of the graph induced from two deletion ( ) channel [ 14 ].…”
Section: Preliminariesmentioning
confidence: 99%
“…A rich body of theoretical and applied algorithmic research has been devoted to the exact solution of the Vertex Cover problem [5,23,32,33]. A standard 2-way branching algorithm can test whether a graph G has a vertex cover of size k in time O(2 k (n + m)), which can be improved by more sophisticated techniques [14].…”
Section: Introductionmentioning
confidence: 99%